1988
DOI: 10.1128/iai.56.6.1602-1607.1988
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin-associated protein: a potent stimulus for human granulocytopoietic activity which may be accessory cell independent

Abstract: Proteins coextracted with endotoxin, termed endotoxin-associated protein (EAP), have been shown to exert interleukin 1-like activities. The present studies demonstrate that EAP also exerts potent granulopoietic colony-stimulating activity (CSA) on human peripheral blood and bone marrow progenitor cells, comparable to that seen with various types of conditioned media. The CSA observed with EAP appeared to be heat (100°C, 30 min) and trypsin resistant and partially pronase resistant. Similar resistance was obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
1

Year Published

1989
1989
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 30 publications
2
8
1
Order By: Relevance
“…LPS is considered to favor the trimerization of gonococcal porin and to be essential for the insertion of porin into mem-branes as was previously reported for the Escherichia coli outer membrane protein PhoE (13,34). However, endotoxin-associated proteins are known to be potent stimuli for human phagocytes (9). Thus, we favor an explanation in which LPS facilitates the priming of neutrophils by porin.…”
Section: Discussionsupporting
confidence: 63%
“…LPS is considered to favor the trimerization of gonococcal porin and to be essential for the insertion of porin into mem-branes as was previously reported for the Escherichia coli outer membrane protein PhoE (13,34). However, endotoxin-associated proteins are known to be potent stimuli for human phagocytes (9). Thus, we favor an explanation in which LPS facilitates the priming of neutrophils by porin.…”
Section: Discussionsupporting
confidence: 63%
“…These findings have been largely confirmed by Porat et al (173), who isolated LAP from E. coli. However, these workers reported that in contrast to the studies of Johns and coworkers (12,104), T cells partially mediated the effect of the LAP and that the formation of granulocyte/macrophage colonies induced by LAP could be blocked by a neutralizing antiserum to IL-1␤. Porat et al also reported that the active protein in the LAP preparation had a molecular mass of 17 kDa (173).…”
Section: Proteinsmentioning
confidence: 77%
“…LAP were also found to be active in the lymphocyte-activating factor assay and to act as a costimulatory factor for the proliferation of resting human T lymphocytes. LAP were also shown to be capable of inducing the formation of granulopoietic colonies when added to human peripheral blood and bone marrow progenitor cells which had been depleted of accessory cells (monocytes and T and B lymphocytes) (12). These workers also confirmed the great stability of the LAP inasmuch as heating to 100ЊC for 30 min or exposure to trypsin or pronase for 24 h at 37ЊC did not decrease the biological activity of these proteins.…”
Section: Proteinsmentioning
confidence: 79%
“…The proteinaceous components of endotoxin, known as lipid A‐associated proteins or endotoxin‐associated proteins, are a family of proteins that bind to lipopolysaccharide in the cell wall of gram‐negative bacteria (1). The lipid A‐associated proteins were first recognized when it was discovered that the B‐cell mitogenic activity of Escherichia coli endotoxin in the lipopolysaccharide‐unresponsive C3H/HeJ mouse depended on the protein content of the endotoxin (2).…”
mentioning
confidence: 99%